A descriptive video analysis of interactions during inpatient brain injury rehabilitation groups. (February 2022) - Patterson, Freyr; Doig, Emmah; Marshall, Kathryn; Fleming, Jennifer
Introduction: An advantage of using groups in rehabilitation is the opportunity for peer learning and support. This study aimed to describe and understand the nature of interactions occurring in inpatient occupational therapy brain injury rehabilitation groups, using video-recorded group interactions, to inform recommendations for group facilitation. Method: Video recordings of four occupational therapy rehabilitation groups were taken. Twelve adults with brain injury who participated in the groups and four facilitators consented to the study. The data were analysed using a qualitative descriptive approach. Results: Interactions were predominantly facilitated by facilitators and shaped by the nature of the group activities. Facilitators used a number of strategies to encourage interaction including knowledge of group participants, activity choice and physical positioning of group members. Conclusion: Group facilitators utilise a number of strategies to encourage peer interactions. However, during structured activity-based rehabilitation groups, participants with a brain injury may focus predominantly on achieving the goal of the group rather than initiating peer interactions.